Solvent Effect, Photochemical and Photophysical Properties of Phthalocyanines with Different Metallic Nuclei - Charles Biral Silva; Anderson Orzari Ribeiro; Hueder Paulo Moisés de Oliveira (Orbital: The Electronic Journal of Chemistry, 2017)
Photophysical and photochemical properties of lithium phthalocyanine (1), gallium(III) phthalocyanine chloride (2), titanium(IV) phthalocyanine dichloride (3) and iron(II) phthalocyanine (4) were investigated in dimethyl sulfoxide (DMSO), tetrahydrofuran (THF) and DMSO-THF mixtures. The influence of the central metal on these properties was analyzed according to solvent type, axial ligands and their paramagnetic and diamagnetic effect. Fluorescence lifetimes were recorded using a time correlated single photon counting setup (TCSPC) technique. In order to demonstrate the generation of reactive oxygen species under light irradiation, the indirect method (applying 1,3-diphenylisobenzofuran (DPBF) as chemical suppressor) and the direct method (analyzing the phosphorescence decay curves of singlete oxygen at 1270 nm) were employed. Compounds 1, 2 and 3 showed a monomeric behavior in all media while compound 4 presented low aggregation in DMSO, but a very pronounced aggregation behavior in THF. Steady-state fluorescence anisotropy was compared with emission spectra and complex 4 presented values beyond the expected limits.DOI: http://dx.doi.org/10.17807/orbital.v9i5.1047